2019
DOI: 10.1002/job.2370
|View full text |Cite
|
Sign up to set email alerts
|

Do not like it when you need it the most: Examining the effect of manager ego depletion on managerial voice endorsement

Abstract: Summary This paper advances the understanding of managerial voice endorsement based on a self‐regulation perspective. We suggest that although managers might potentially benefit more from employees' upward voice when they are more depleted, they are paradoxically less likely to diligently process or endorse such voice under ego depletion. We draw from ego depletion theory and argue that when managers are more depleted of their self‐control resources, they will spend less cognitive effort in processing voice. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 67 publications
0
68
0
2
Order By: Relevance
“…Burdened with multiple difficult issues in daily work, leaders face the same dilemma, or even worse. They have to take on challenging tasks and at the same time deal with complex interpersonal relationships, which significantly tax their limited resources (Li, Barnes, Yam, Guarana, & Wang, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Burdened with multiple difficult issues in daily work, leaders face the same dilemma, or even worse. They have to take on challenging tasks and at the same time deal with complex interpersonal relationships, which significantly tax their limited resources (Li, Barnes, Yam, Guarana, & Wang, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In addition to the influence of the message, the voice sender and receiver may also affect voice endorsement [ 7 ]. In a recent study, Li et al (2019) showed that employee voice was more likely to be endorsed by managers with low ego depletion than by managers with high ego depletion [ 11 ]. However, we still need more systematic evidence to deepen the understanding of how the interplay between the voice sender and receiver affects voice endorsement.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, our studies did not investigate underlying mechanisms that can explain why the interaction between leaders' performance-approach goals and sense of power leads to differences in leader receptivity. Therefore, future research may investigate process mechanisms such as image threat appraisal (Sijbom et al, 2015a) and effort in processing the idea (Li et al, 2019) that may explain the moderating effects we found in the present research.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 87%
“…Fourth, we investigated leader receptivity to voiced ideas. Although, receptivity is an important first step of idea endorsement, further steps need to be taken to implement voiced creative ideas (Burris, 2012;Li et al, 2019). These steps include getting more detailed information to further validate the idea, evaluating the pros and cons, and considering whether the idea is feasible in terms of available resources.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%